Albumin in Tears Modulates Bacterial Susceptibility to Topical Antibiotics in Ophthalmology - Sebbag, Lionel; Broadbent, Victoria L.; Kenne, Danielle E.; Perrin, Ashtyn L.; Mochel, Jonathan P. (Frontiers in Medicine, 2021)
Bacterial keratitis is a serious and vision-threatening condition in veterinary and human patients, one that often requires culture and susceptibility testing to adjust therapy and improve clinical outcomes. The present study challenges the antimicrobial susceptibility testing (AST) paradigm in ophthalmology, enabling more accurate in vitro-to-in vivo translation by incorporating factors normally present during host-pathogen interactions in clinical patients. Thirty bacteria (10 Staphylococcus pseudintermedius, 10 Streptococcus canis, 10 Pseudomonas aeruginosa) were isolated from canine patients with infectious keratitis. For each isolate, commercial plates (SensititreTM JOEYE2) were used to assess the minimal inhibitory concentration (MIC) of 17 different antibiotics in the absence (0% albumin, control) or presence of canine albumin (0.01-2%). For Staphylococcus pseudintermedius, the experiment was repeated with actual tear fluid collected from canine eyes with ocular surface inflammation. Kruskal-Wallis, Wilcoxon signed rank test and Spearman’s correlation tests were used for statistical analysis. Clinical outcomes were unfavorable in selected canine patients with bacterial keratitis (eg., globe perforation, graft dehiscence) despite standard AST (ie., 0% albumin in test medium) confirming that most corneal infections (93%) were susceptible to ≥ 1 topical antibiotics used at the initial visit. Albumin levels ≥ 0.05% increased MICs in a dose-dependent, bacteria-specific, and antibiotic-specific manner. No significant differences (P = 1.000) were noted in MICs of any antibiotic whether albumin or tear fluid was added to the Mueller-Hinton broth. Percent protein binding inherent to each antibiotic was associated with clinical interpretations (Spearman’s rho = -0.53, P = 0.034) but not changes in MICs. Albumin in tears impacted the efficacy of selected ophthalmic antibiotics as only the unbound portion of an antibiotic is microbiologically active. The present findings could improve decision making of clinicians managing bacterial keratitis, reduce development of antimicrobial resistance, influence current guidelines set by the Clinical and Laboratory Standards Institute, and serve as a reference for bacteriological evaluations across medical fields and across species.